1eve in Miao Village : modern business logic of Chinese traditional handicraft - Jingyue, Xu; Ooi, Sue Chern; Chung, Muh Sha (London : Renmin University, 2022)
This case describes how Eve Group, a leading, enterprise in China's fashion industry, has discovered, sorted out, innovated and applied Chinese traditional handicrafts scattered around the country since 2003. They created a platform for the inheritance and empowerment of Chinese traditional handicrafts and Oriental aesthetic culture - Eve Chinese Handicraft Workshop. This case aims to guide students to think about whether and how to achieve win-win between business value and social responsibility. Through discussion, students will learn that companies should focus on creating Shared Value for all stakeholders, not just for shareholders. They will learn how strategic corporate social responsibility is used to create Shared Value for companies and society and form a virtuous circle. The case also provides students a context to think about the challenges of future business development from the perspective of the founder.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cultural industries -- China; Social responsibility of business; Business planning -- China